ENERGY GAP ANALYSIS OF BA0.25SR0.75TIO3 THIN FILM ON GLASS INDIUM TIN OXIDE (ITO) SUBSTRATE - Rony Febryarto; Novia Fransiska Simbolon; Dea Widiawati; Naila Nur Alifa; Irzaman (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
Ba₀.₂₅Sr₀.₇₅TiO₃ (BST) thin films were fabricated on indium tin oxide (ITO) glass substrates using the chemical solution deposition (CSD) method followed by annealing. The objective of this work was to investigate the effect of Ruthenium (Ru) doping on the optical properties, particularly the band gap energy, of BST thin films. Optical characterization was carried out using UV–Vis spectrophotometry in the wavelength range of 230–850 nm. The results revealed that Ru doping effectively modified the electronic structure of BST, leading to a progressive reduction in band gap energy. On silicon substrates, the band gap decreased from 3.363 eV (undoped) to 1.568 eV (1.5% Ru), while on ITO substrates it decreased from 2.116 eV to 1.698 eV for the same doping level. This decreasing trend indicates that Ru introduces localized states or defect levels within the BST structure, facilitating electronic transitions at lower photon energies. The tunability of the band gap is highly significant for optoelectronic applications. A narrower band gap enhances light absorption in the visible region, which is beneficial for devices such as solar cells, photodetectors, optical sensors, and smart windows. Furthermore, the compatibility of BST with transparent conducting oxides such as ITO strengthens its potential forintegration into multifunctional and energy-efficient devices. In summary, this study demonstrates that Ruthenium doping provides a promising route to tailor the band gap of BST thin films, thereby expanding their applicability in next-generation optoelectronic technologies.